Empagliflozin reduces podocyte lipotoxicity in experimental Alport syndrome - Mengyuan Ge; Judith Molina; Jin-Ju Kim; Shamroop K Mallela; Anis Ahmad; Javier Varona Santos; Hassan Al-Ali; Alla Mitrofanova; Kumar Sharma; Flavia Fontanesi; Sandra Merscher; Alessia Fornoni (eLife, 2023)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are anti-hyperglycemic agents that prevent glucose reabsorption in proximal tubular cells. SGLT2i improves renal outcomes in both diabetic and non-diabetic patients, indicating it may have beneficial effects beyond glycemic control. Here, we demonstrate that SGLT2i affects energy metabolism and podocyte lipotoxicity in experimental Alport syndrome (AS). In vitro, we found that the SGLT2 protein was expressed in human and mouse podocytes to a similar extent in tubular cells. Newly established immortalized podocytes from Col4a3 knockout mice (AS podocytes) accumulate lipid droplets along with increased apoptosis when compared to wild-type podocytes. Treatment with SGLT2i empagliflozin reduces lipid droplet accumulation and apoptosis in AS podocytes. Empagliflozin inhibits the utilization of glucose/pyruvate as a metabolic substrate in AS podocytes but not in AS tubular cells. In vivo, we demonstrate that empagliflozin reduces albuminuria and prolongs the survival of AS mice. Empagliflozin-treated AS mice show decreased serum blood urea nitrogen and creatinine levels in association with reduced triglyceride and cholesterol ester content in kidney cortices when compared to AS mice. Lipid accumulation in kidney cortices correlates with a decline in renal function. In summary, empagliflozin reduces podocyte lipotoxicity and improves kidney function in experimental AS in association with the energy substrates switch from glucose to fatty acids in podocytes.